2008
DOI: 10.1631/jzus.b0710603
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of high-yield performance as affected by genotype and environment in rice

Abstract: Abstract:We characterized yield-relevant characters and their variations over genotypes and environments (locations and years) by examining two rice varieties (9746 and Jinfeng) with high yield potential. 9746 and Jinfeng were planted in two locations of Shanghai, China, during 2005 and2006. The results show that there was a large variation in grain yield between locations and years. The realization of high yield potential for the two types of rice was closely related to the improved sink size, such as more pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 14 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…This might suggest that qTSN4 effects on panicle size are not directly controlled by qTSN4 but indirectly via whole-plant assimilate source-sink relations. If its effect on panicle size is indirect, we can expect it to be (1) highly prone to GxE interactions (Zhuang et al 1997 ; Kobayashi et al 2004 ; Chen et al 2008 ), (2) non-specific with respect to panicle architectural traits (conservation of structural allometric relationships as panicle size varies), and (3) associated with pre-floral growth rate which is known to physiologically control panicle size (Horie et al 2003 ; Kamiji et al 2011 ). To test these hypotheses, we challenged NILs for qTSN4 with variable light resources, focused on structural panicle traits and determined their relationship with pre-floral growth rates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This might suggest that qTSN4 effects on panicle size are not directly controlled by qTSN4 but indirectly via whole-plant assimilate source-sink relations. If its effect on panicle size is indirect, we can expect it to be (1) highly prone to GxE interactions (Zhuang et al 1997 ; Kobayashi et al 2004 ; Chen et al 2008 ), (2) non-specific with respect to panicle architectural traits (conservation of structural allometric relationships as panicle size varies), and (3) associated with pre-floral growth rate which is known to physiologically control panicle size (Horie et al 2003 ; Kamiji et al 2011 ). To test these hypotheses, we challenged NILs for qTSN4 with variable light resources, focused on structural panicle traits and determined their relationship with pre-floral growth rates.…”
Section: Discussionmentioning
confidence: 99%
“…Both spikelet number and stem growth rates between PI and flowering were larger in the field than in GH, and the correlation across factors was particularly strong for the NILs having IRRI146 background, which also showed the more consistent qTSN4 effect. In addition, Sheehy et al ( 2001 ), Takai et al ( 2006 ) and Chen et al ( 2008 ) reported that biomass accumulation in the stem (including leaf sheath) during panicle development contributes to panicle spikelet number. Also, spikelet number shares a common genetic basis with above-ground biomass (Zhang et al 2004 ) and crop growth rate at 14 days before heading (Horie et al 2003 , Kamiji et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…Rice plants grown in presence of hydrolyzate filtrate, and feather hydrolyzate with bioinoculant showed higher number of tillers per plant over other treatments. The tillering number is one of the most important indicators of crop yield potential as it is closely related with the number of panicles per unit area in the rice plants . Similarly, Kim et al reported that feather digests exhibited the same growth effect as that of N fertilizer on carrot and Chinese cabbage.…”
Section: Biofertilizing Potentialmentioning
confidence: 99%
“…Grain yield elaboration in cereals depends on the establishment of panicle number per square meter and panicle size, grain filling rate, and individual grain size (Chen et al, 2008 ; Gaju et al, 2014 ). All these traits are known to compensate per unit area i.e., among plants (Zhang and Yamagishi, 2010 ) and within the plant where they compete for the same pool of C and N resources (Okawa et al, 2003 ; Hashida et al, 2013 ).…”
Section: Introductionmentioning
confidence: 99%